Joint developmental trajectories of depressive symptoms, perceived stress in adolescence and their relationship with smartphone addiction - Zhang, Cai; Zhang, Zhiqian; Lei, Hanning; Wang, Xia; Wang, Yun (Frontiers in Psychiatry, 2025)
IntroductionMental health issues frequently cluster during adolescence, necessitating a deeper understanding of their developmental trajectories and their impact on behavioral outcomes like smartphone addiction. Based on diathesis-stress model and I-PACE model, this study examined the joint trajectories of depressive symptoms, family stress perception, and academic stress perception among adolescents and their relationship with smartphone addiction.Methods12,074 Chinese adolescents (47.9% girls; Mage = 12.28 ± 0.45 years) were assessed for depressive symptoms, perceived family stress and academic stress from seventh to ninth grade, with smartphone addiction measured in the final year.ResultsUsing a group-based multi-trajectory model, five distinct trajectories were identified: Low-Stable (23.8%), Moderate-Stable (45.9%), Moderate-Increasing (14.8%), High-Decreasing (11.2%), and High-Stable (4.3%). Gender differences were evident, as girls were more likely than boys to belong to higher stress or depressive symptoms trajectories compared to the low-stable group. Smartphone addiction scores differed significantly across trajectory groups, ranging from high-stable to low-stable. Girls consistently showed higher smartphone addiction scores, although the interaction between gender and trajectory group was not significant.ConclusionThese findings highlight the importance of recognizing both shared and individual patterns of adolescent mental health development. Schools and families should implement tailored interventions to address depression and stress, particularly for vulnerable groups such as girls, to mitigate the risk of smartphone addiction and promote overall mental well-being.